Racist attitudes, out‐groups and the Australian experience. Issue 1 (15th April 2020) - Forrest, James; Blair, Kathleen; Dunn, Kevin
Abstract: Australia today is a culturally diverse nation with people from over 190 different countries claiming 300 different ancestries. But despite an official commitment to diversity, contemporary Australian society continues to experience tensions between multicultural policies and a legacy of Anglo privilege and cultural dominance. To assess this, the Challenging Racism Project conducted a national survey, commissioned by the Special Broadcasting Service, to gauge the nature and extent of racist attitudes and experience of racism across Australia during July–August 2015 and November 2015. Results show that sociodemographic characteristics show little contemporary relationship to racist attitudes. Age, once associated with "old" racist attitudes, is no longer significant. On the other hand, Anglo privilege is empirically linked to racism through notions of social dominance. We conclude that it is to the media, and to public discourse generally, to which future research attention, using critical discourse analysis, should turn in efforts to make Australia a fairer, more tolerant, multicultural society.